Overexpression of WNT2 and TSG101 genes in colorectal carcinoma - Ma, Xiang Ru; Sim, Edmund U. H.; Balraj, Pauline; Lim, Patricia; Rahman, Jamal (Malaysian Society of Parasitology and Tropical Medicine, 2008)
Colorectal carcinoma (CRC) arises as a result of mutational activation of oncogenes coupled with inactivation of tumour suppressor genes. Mutations in APC, K-ras and p53 have been commonly reported. In a previous study by our group, the tumour susceptibility gene 101 (TSG101) were found to be persistently upregulated in CRC cases. TSG101 was reported to be closely related to cancers of the breast, brain and colon, and its overexpression in human papillary thyroid carcinomas and ovarian carcinomas had previously been reported. The wingless-type MMTV integration site family member 2 (WNT2) is potentially important in the Wnt/β-catenin pathway and upregulation of WNT2 is not uncommon in human cancers. In this study, we report the investigation for mutation(s) and expression pattern(s) of WNT2 and TSG101, in an effort to further understand their role(s) in CRC tumourigenesis. Our results revealed no mutation in these genes, despite their persistent upregulation in CRC cases studied.